The effectiveness of AI-assisted learning platforms on students’ critical thinking and academic performance in higher education - Zulkifli Rangkuti; Suhaimi Suhaimi; Dedi Irawan; Nurita Putranti; Khoiriyah Khoiriyah (Indonesian Institute For Counseling, Education and Therapy, 2026)
Artificial intelligence-assisted learning platforms have increasingly transformed higher education by providing personalized learning experiences and adaptive instructional support. However, evidence regarding their effectiveness in enhancing students' critical thinking and academic performance has remained fragmented across different research streams. This study aimed to synthesize contemporary evidence on the educational effectiveness of artificial intelligence-assisted learning platforms in higher education. A qualitative library research approach was employed by reviewing and thematically analyzing 39 scholarly publications on artificial intelligence in education, critical thinking, academic performance, learning analytics, intelligent tutoring systems, and ethical artificial intelligence implementation. The findings indicated that artificial intelligence-assisted learning platforms enhanced learning effectiveness through personalized learning pathways, adaptive feedback, learning analytics, and human–artificial intelligence collaboration. These mechanisms supported the development of critical thinking and improved academic performance when implemented within sound pedagogical practices. The synthesis also revealed that ethical governance, academic integrity, transparency, privacy protection, and digital literacy were essential conditions for sustainable and responsible artificial intelligence integration. This study proposed an integrated conceptual framework that explained the relationships among technological, pedagogical, and ethical dimensions of artificial intelligence-assisted learning. The findings provided theoretical insights and practical guidance for higher education institutions seeking to implement artificial intelligence to improve learning quality and student outcomes.